Development and Utility of an Interactive Online Dashboard for Monitoring Data Collection and Data Processing During a School-Based Health Survey. - Tan, LeeAnn; Ganapathy, Shubash Shander; Kuang Kuay Lim; Ahmad, Noor Ani (Journal of Public Health Management & Practice)
We built an interactive online dashboard using Google Looker Studio to monitor data collection and data processing activities during the Adolescent Health Survey (AHS) 2022, a large-scale nationwide survey conducted among schoolgoing adolescents in Malaysia. Through user testing and training, refinements were made to the initial dashboard, resulting in a more streamlined and concise dashboard design. The dashboard comprised 2 pages that provided key metrics on the progress of data collection and data processing, respectively. The introduction of the dashboard enhanced the quality and ease of weekly progress reporting during meetings of the survey's central coordinating team, while its drill-down and filtering functionalities helped us detect arising issues early and supported collaborative problem-solving. Research teams coordinating comparable school-based health surveys are invited to duplicate the dashboard using Looker Studio's built-in "Make a copy" function and customize it further based on their country- or survey-specific requirements.